Using the property of equality, What first step would you take to rearrange the formula y=mx+b using x As the quantity of interest

1 answer

To rearrange the formula \( y = mx + b \) for \( x \) as the quantity of interest, you should isolate \( x \) on one side of the equation. Here are the steps:

  1. Subtract \( b \) from both sides to get rid of the constant term: \[ y - b = mx \]

  2. Next, divide both sides by \( m \) to solve for \( x \): \[ x = \frac{y - b}{m} \]

Now you have \( x \) expressed in terms of \( y \), \( m \), and \( b \): \[ x = \frac{y - b}{m} \]